Evidence of immunocompetence reduction induced by cadmium exposure in honey bees (Apis mellifera). (November 2016) - Polykretis, P.; Delfino, G.; Petrocelli, I.; Cervo, R.; Tanteri, G.; Montori, G.; Perito, B.; Branca, J.J.V.; Morucci, G.; Gulisano, M.
Abstract: In the last decades a dramatic loss of Apis mellifera hives has been reported in both Europe and USA. Research in this field is oriented towards identifying a synergy of contributing factors, i.e. pathogens, pesticides, habitat loss and pollution to the weakening of the hive. Cadmium (Cd) is a hazardous anthropogenic pollutant whose effects are proving to be increasingly lethal. Among the multiple damages related to Cd contamination, some studies report that it causes immunosuppression in various animal species. The aim of this paper is to determine whether contamination by Cd, may have a similar effect on the honey bees' immunocompetence. Our results, obtained by immune challenge experiments and confirmed by structural and ultrastructural observations show that such metal causes a reduction in immunocompetence in 3 days Cd exposed bees. As further evidence of honey bee response to Cd treatment, Energy Dispersive X-ray Spectroscopy (X-EDS) has revealed the presence of zinc (Zn) in peculiar electron-dense granules in fat body cells. Zn is a characteristic component of metallothioneins (MTs), which are usually synthesized as anti-oxidant and scavenger tools against Cd contamination. Our findings suggest that honey bee colonies may have a weakened immune system in Cd polluted areas, resulting in a decreased ability in dealing with pathogens. Graphical abstract: Highlights: Cadmium exposure causes a substantial immunocompetence reduction in honey bees. Cadmium exposure causes severe cellular damage in honey bee fat bodies. Trophocytes of Cd exposed bees exhibit a remarkable presence of peculiar cellular inclusions. The high amount of Zn in such cellular inclusions is presumably attributable to metallothioneins. Honey bee hives may have difficulty in dealing with pathogens in Cd polluted areas. Abstract : Cadmium exposure causes a substantial immunocompetence reduction in honey bees and a severe damage in immunity-related tissues of the insect.